1990
DOI: 10.1104/pp.93.4.1441
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide Chlorsulfuron Decreases Assimilate Transport Out of Treated Leaves of Field Pennycress (Thlaspi arvense L.) Seedlings

Abstract: Treatment of field pennycress (Thiaspi arvense L.) leaves with the herbicide chlorsulfuron resulted in a decrease in the export of assimilate. Twelve hours after a spot application of 1 microgram, assimilate translocation was 70% of that in control leaves. In excised leaves treated with chlorsulfuron the total amounts of sugars and free amino acids were 150 and 170%, respectively, of the amounts in control leaves, 30 hours after herbicide treatment. The amount of sucrose was 247% of that in control leaves. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
1
4

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 21 publications
5
41
1
4
Order By: Relevance
“…This occurs as a consequence of the deregulation of carbon metabolism and increased carbon flow into the shikimate pathway following the inhibition of 5-enolpyruvylshikimate-3-phosphate synthase, the herbicide target site (Steinrü cken and Amrhein, 1980;Gougler and Geiger, 1984;Geiger et al, 1986Geiger et al, , 1987. Chlorsulfuron, on the other hand, does not reduce carbon fixation or hexose/Suc synthesis, but prevents Suc loading in source leaf tissue (Bestman et al, 1990;Devine et al, 1990;Hall and Devine, 1993). Therefore, the phloem mobility of chlorsulfuron was considerably greater in an Arabidopsis mutant with a resistant form of acetolactate synthase (the herbicide target site [Ray, 1984]) than in a susceptible biotype (Hall and Devine, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…This occurs as a consequence of the deregulation of carbon metabolism and increased carbon flow into the shikimate pathway following the inhibition of 5-enolpyruvylshikimate-3-phosphate synthase, the herbicide target site (Steinrü cken and Amrhein, 1980;Gougler and Geiger, 1984;Geiger et al, 1986Geiger et al, , 1987. Chlorsulfuron, on the other hand, does not reduce carbon fixation or hexose/Suc synthesis, but prevents Suc loading in source leaf tissue (Bestman et al, 1990;Devine et al, 1990;Hall and Devine, 1993). Therefore, the phloem mobility of chlorsulfuron was considerably greater in an Arabidopsis mutant with a resistant form of acetolactate synthase (the herbicide target site [Ray, 1984]) than in a susceptible biotype (Hall and Devine, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…It would be incorrect to assume that a relatively large organic molecule, such as an herbicide, would prefer to cross two cell walls and two plasma membranes instead of being carried by a continuous cytoplasmic tube between cells in the same domain. Another study describes the application of 10 droplets of chlorsulfuron on the third definitive leaf of a seedling of field pennycress (Thlaspi arvense) with five definitive leaves (Bestman et al, 1990). Chlorsulfuron is an herbicide that belongs to the group of sulfonylurea, inhibitor of the enzyme acetolactate synthase (ALS), involved in the synthesis of branched-chain amino acid valine, leucine, and isoleucine (Leite et al, 1998).…”
Section: Herbicide Translocation Through Plasmodesmatamentioning
confidence: 99%
“…For example, S h i m et al [13] reported an increase in free amino acid content with an increasing dose of azimsulfuron and explained it by the reactivation of metabolic pathways leading to the introduction of compounds that had been received from amino acid degradation. B e s t m a n et al [14] also proved an increase in free amino acid content after chlorsulfuron application as a result of secondary transformation of amino acids and proteins in plants. Amino acid content may also be affected by environmental stress, i.e.…”
Section: Introductionmentioning
confidence: 99%